2014
DOI: 10.1089/neu.2013.3223
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Gap Junction Hemichannel Protects Secondary Spinal Cord Injury from Activated Microglia-Mediated Glutamate Exitoneurotoxicity

Abstract: We previously demonstrated that activated microglia release excessive glutamate through gap junction hemichannels and identified a novel gap junction hemichannel blocker, INI-0602, that was proven to penetrate the blood-brain barrier and be an effective treatment in mouse models of amyotrophic lateral sclerosis and Alzheimer disease. Spinal cord injury causes tissue damage in two successive waves. The initial injury is mechanical and directly causes primary tissue damage, which induces subsequent ischemia, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Animal model studies have also shown that Cx43 hemichannel blockade reduced infarct size after myocardial infarction (Hawat et al, 2012; Wang et al, 2013) and decreased glial scarring in both ischemic stroke (Davidson et al, 2015) and spinal cord injury models (Umebayashi et al, 2014). In the context of skin healing and hypertrophic scarring or keloid formation, modulation of Cx43 expression levels has been shown to control the balance between fibroblast proliferation and apoptosis, as well as extracellular matrix deposition (Lu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Animal model studies have also shown that Cx43 hemichannel blockade reduced infarct size after myocardial infarction (Hawat et al, 2012; Wang et al, 2013) and decreased glial scarring in both ischemic stroke (Davidson et al, 2015) and spinal cord injury models (Umebayashi et al, 2014). In the context of skin healing and hypertrophic scarring or keloid formation, modulation of Cx43 expression levels has been shown to control the balance between fibroblast proliferation and apoptosis, as well as extracellular matrix deposition (Lu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the use of a derivative of CBX, INI‐0602, which inhibits glutamate release from microglial cells by blocking activated Cx32 HCs, improved memory impairment in another FAD mouse model (Takeuchi et al, ). This drug also led to behavioral amelioration in other models of neurodegenerative diseases, ALS and PD (Suzuki, Ono, & Sawada, ; Takeuchi et al, ), and in spinal cord injury (Umebayashi et al, ). The underlying mechanisms were attributed to the inhibitory effect of INI‐0602 on microglial Cx32 HCs (Takeuchi et al, ) although direct evidence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In the uninjured adult brain, microglial cells typically have a small cell body endowed with numerous radial extensions, which are highly ramified. Microglial cells occupy cellular microdomains which do not overlap, and which accordingly are only sparsely interconnected by junctions, although they are equipped with gap junctional hemichannels (Orellana et al, 2009;Umebayashi et al, 2014). Such cells were formerly termed 'resting' or 'quiescent' microglia.…”
Section: Morphological and Functional Signs Of Microglial Activationmentioning
confidence: 99%